Resting state connectivity differences in eyes open versus eyes closed conditions - Agcaoglu, Oktay; Wilson, Tony W.; Wang, Yu‐Ping; Stephen, Julia; Calhoun, Vince D. (Human brain mapping, 2019)
Functional magnetic resonance imaging data are commonly collected during the resting state. Resting state functional magnetic resonance imaging (rs‐fMRI) is very practical and applicable for a wide range of study populations. Rs‐fMRI is usually collected in at least one of three different conditions/tasks, eyes closed (EC), eyes open (EO), or eyes fixated on an object (EO‐F). Several studies have shown that there are significant condition‐related differences in the acquired data. In this study, we compared the functional network connectivity (FNC) differences assessed via group independent component analysis on a large rs‐fMRI dataset collected in both EC and EO‐F conditions, and also investigated the effect of covariates (e.g., age, gender, and social status score). Our results indicated that task condition significantly affected a wide range of networks; connectivity of visual networks to themselves and other networks was increased during EO‐F, while EC was associated with increased connectivity of auditory and sensorimotor networks to other networks. In addition, the association of FNC with age, gender, and social status was observed to be significant only in the EO‐F condition (though limited as well). However, statistical analysis did not reveal any significant effect of interaction between eyes status and covariates. These results indicate that resting‐state condition is an important variable that may limit the generalizability of clinical findings using rs‐fMRI.